Utilizing Coal ash and Lignite Enriched-Compost to Improve Chemical Properties of Ultisols - Fadil Fajarindo; Suwardi Suwardi; Iskandar Iskandar; Atfritedy Limin (UNIVERSITY OF LAMPUNG, 2024)
Continuous monoculture activities can cause soil degradation, leading to low pH, organic matter content, and nutrient deficiencies in Ultisols. Compost has been used to improve soil fertility. Unfortunately, its effectiveness has been limited due to rapid decomposition in the humid tropic area. This study investigated the effect of adding coal ash (fly ash and bottom ash or abbr. as FABA) and lignite to compost on the chemical properties of degraded Ultisols planted with pineapple. The study was conducted at Pineapple plantation in Central Lampung using a split-plot design. The application technique (row or spread) was the main plot and three treatments as subplots were 100% compost (K), 75% compost + 25% FABA (KF), and 70% compost + 20% FABA + 10% lignite (KFL). Each treatment was applied at a dose of 50 Mg ha-1. The results showed that adding FABA and lignite to compost effectively increased the organic carbon, pH, base saturation, exchangeable calcium, -magnesium, -sodium, and zinc, decreasing the aluminum saturation of Ultisols. The application of ameliorants in rows technique was more effective than those of spreading. These findings suggest that FABA and lignite-enriched compost in row application can effectively improve the chemical properties of degraded Ultisols.